The ignition and combustion characteristics of Al/Ni(IO3)2·4H2O nanothermites. Issue 4 (2nd October 2019) - Mei, Xinliang; Zhong, Gaoyan; Cheng, Yi
ABSTRACT: Nickel iodate tetrahydrate (Ni(IO3 )2 ·4H2 O) particles with different morphology and size were synthesized by precipitation method (PM) and electrospray precipitation method (EPM). The electrospray was used in chemical precipitation to synthesize nanoscale metal iodate particles with a narrow size distribution. The thermal decomposition mechanism of Ni(IO3 )2 ·4H2 O at different heating rates, ignition, and combustion of Al/Ni(IO3 )2 ·4H2 O nanothermites was studied by thermogravimetry–differential scanning calorimetry–mass spectrometry, T-jump and time-of-flight mass spectrometry, T-jump equipped with high-speed camera, and combustion cell test. The Al/Ni(IO3 )2 ·4H2 O prepared by EPM had a lower ignition temperature (587 ± 14°C) and a shorter burn time (159 µs). The ignition processes of Al/Ni(IO3 )2 ·4H2 O nanothermites prepared by EPM and PM were solid–solid and gas–liquid reactions, respectively. The rate-determining step of their combustion processes was the burning of aluminum powder and the decomposition of Ni(IO3 )2 · 4H2 O, respectively.